Un nuovo framework per le analisi di bilancio un “check-up veloce” con l’indice-M - Mella, Piero; Meo Colombo, Carlotta; Navaroni, Matteo (Piccola Impresa / Small Business, 2011)
This study starts from the assumption that the analysis of financial statements– in particular, those for indices – according to the traditional theoretical framework accepted in the literature, are based on an operational logic which can be summarized as follows: if the management of the firm – which entails operations, arranged into processes and coordinated activities, which derive from the rational Economic Calculations of management and are continually revised based on variations in the operational and competitive context in which the firm operates – produces a system of values for production, costs, investments and financing, and if these values reflect the financial statement regarding the income and capital highlights, then this document is not only a simple report but can become the basis for deriving a coordinated system of indicators that permit the construction of a managerial model of the firm and the appreciation of the firm’s performance and fitness. To deal with the problem of how to attribute a descriptive value to the indicators, this study considers a different approach: if we postulate that the management of the firm, and thus the financial statement values, derives from the rational economic calculation, then we can also postulate several rational rules which must be followed by management in order to produce a “good management” of the firm. In this manner, 18 fundamental Postulates of “good management” are identified, from which a global indicator is constructed, called Index-M, which can be used for a concise appraisal, a fast check-up, of the firm’s performance and fitness. Index-M is validated through the application of simulated financial statements.